ANALISIS KEPEMILIKAN DATA PRIBADI SEBAGAI HAK SUBSTANTIF DALAM SISTEM HUKUM INDONESIA - Varany, Yacinta Tira (Ensiklopedia of Journal, 2025)
Personal data has become the “new currency” of the digital era, representing both economic value and the existential identity of modern humans. Every digital activity ranging from online searches and social media interactions to economic transactions produces data traces that construct an individual’s unique profile in cyberspace. Ironically, data generated by individuals are often controlled, stored, and monetized by external parties without full authority resting with the original owner. This raises a fundamental question: does an individual still possess the right to self-determination in the digital realm, or has the person become merely a source of data for the interests of algorithms and global corporations?This study aims to re-examine the legal position of personal data within the Indonesian legal system through a normative juridical approach, analyzing conceptual, regulatory, and philosophical aspects. The focus lies in distinguishing between the right of control and substantive ownership, and in exploring how national law can ensure individual sovereignty over personal data. The findings reveal that although Law No. 27 of 2022 on Personal Data Protection (PDP Law) represents a normative advancement, the prevailing legal paradigm still positions individuals as consent-givers rather than as owners who hold inherent rights to their data.The novelty of this research lies in asserting a new paradigm that recognizes personal data as a form of substantive ownership derived from the inherent right to self. Accordingly, acknowledging personal data ownership is not merely a matter of legal protection, but a civilizational step toward restoring human beings as sovereign subjects over themselves in the digital world. Such recognition would strengthen individuals’ legal standing, close avenues for data exploitation, and uphold informational justice grounded in human dignity. This paradigm is expected to serve as the foundation for legal reform toward a digital legal system that is sovereign, just, and human-centered. Keywords: personal data ownership, substantive rights, digital sovereignty, informational justice, Indonesian law